Methodology for Developing Mathematical Competence of Future Primary School Teachers Through Non-standard Problems. (Scientific journal of the Fergana State University, 2025)
This article explores methodological approaches to developing mathematical competence in future primary school teachers through non-standard problems. The study emphasizes the importance of non-standard problems and their role in fostering students' analytical and creative thinking skills. It also examines ways to strengthen mathematical concepts and enhance the ability to apply theoretical knowledge in practice through solving such problems.